2021
DOI: 10.1038/s41398-021-01636-9
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of effectiveness of real-world studies of antipsychotics in schizophrenia: Are the results consistent with the findings of randomized controlled trials?

Abstract: Randomized controlled trials (RCTs) have been considered as gold standard for establishing the efficacy and safety of investigational new drugs; nonetheless, the generalizability of their findings has been questioned. To address this issue, an increasing number of naturalistic studies and real-world database analyses have been conducted. The question of how much information from these two approaches is congruent or discrepant with each other is of great importance for the clinical practice. To answer this ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Cyamemazine was also associated with a low adherence, but this might be due to the conditions of use of this drug, which can be more easily used as an as-needed treatment, since it targets anxiety or irritability. Regarding other oral antipsychotics, our results are in line with other studies, which found that clozapine was the antipsychotic drug with the highest level of adherence ( 19 ), and that olanzapine, quetiapine, and aripiprazole were associated with low rates of treatment discontinuation, when compared to other antipsychotics ( 20 ). However, our study is the first to confirm this in real-life French data.…”
Section: Discussionsupporting
confidence: 91%
“…Cyamemazine was also associated with a low adherence, but this might be due to the conditions of use of this drug, which can be more easily used as an as-needed treatment, since it targets anxiety or irritability. Regarding other oral antipsychotics, our results are in line with other studies, which found that clozapine was the antipsychotic drug with the highest level of adherence ( 19 ), and that olanzapine, quetiapine, and aripiprazole were associated with low rates of treatment discontinuation, when compared to other antipsychotics ( 20 ). However, our study is the first to confirm this in real-life French data.…”
Section: Discussionsupporting
confidence: 91%
“…One reason for this is the so‐called efficacy‐effectiveness gap, which means that the effectiveness in clinical practice is generally reduced compared to the efficacy shown in RCTs by transfer and implementation loss, for example, delivery of care, adherence to treatment, and time between treatment and assessment of the outcome 32,33 . Nevertheless, consistency between RWD and RCT data was already shown for indications like metastatic renal cell carcinoma when treated with the tyrosine kinase inhibitor sunitinib or the use of antipsychotics in schizophrenia 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…delivery of care, adherence to treatment, and time between treatment and assessment of the outcome (31,32). Nevertheless, consistency between RWD and RCT data were already shown for indications like metastatic renal cell carcinoma when treated with the tyrosine kinase inhibitor sunitinib or the use of antipsychotics in schizophrenia (33,34).…”
Section: Discussionmentioning
confidence: 97%